Social Construction of Teaching Campus 3 (KM 3) at SDN Mragel, Lamongan - Jenny Yudha Utama; Vivi Dwi Permatasari; Tania Febiana; Muhammad Mirza Safaraz (Cita konsultindo, 2022)
Education is the right of all people in accordance with the mandate of the Constitution. In order to create good awareness, character, and personality in students as a provision for life in a society that is growing over time. In an education policy must also follow the times. So that the Ministry of Education and Culture issued an Independent Learning Campus Policy (MBKM) and one of its implementations is the Teaching Campus (KM), so the author wants to examine how social construction is in KM batch 3 at SDN Mragel, Lamongan Regency. The purpose of this writing is to find out the social construction of KM3 at SDN Mragel, Lamongan Regency. The benefit of this writing is as material for evaluating KM 3 activities at SDN Mragel, Lamongan Regency. The theory used is related to social construction belonging to Petter.L. Berger and Luckmann. The method used is qualitative with a case study approach. As for data collection techniques using observation, interviews, and documentation, the results obtained are externalization which is a form of social product carried out by humans who experience processes at SDN Mragel, namely literacy corner, flag ceremony, school administration with digitalization, while objectification is an institutionalization and becomes the objective reality of KM 3 refers to Permendikbud No. 3 of 2020. Internalization of the process of interpreting objects captured by individuals from both the teacher and school principal elements with implementing KM3 and vice versa, students at SDN Mragel with implementing KM 3 and vice versa.